Eliciting public values on health inequalities: missing evidence for policy windows? - McHugh, Neil (Evidence & policy, 2022)
Background:There is a widening health divide in the UK despite health inequalities being a longstanding subject of policy and research. New types of evidence are needed. Key points for discussion:Knowledge of public values for non-health policies and their associated (non-)health outcomes is currently missing from decision-making processes. Eliciting public values using stated preference techniques can provide insights on what the general public would be willing to give up for different distributions of (non-)health outcomes and the policies that can achieve them. To understand the role this evidence could have in decision-making processes, Kingdon’s multiple streams analysis (MSA) is used as a policy lens to explore how evidence of public values could affect policy processes for ways to tackle health inequalities. Conclusions and implications:This paper outlines how evidence of public values could be elicited through the use of stated preference techniques and suggests this could facilitate the creation of policy windows for tackling health inequalities. Additionally, Kingdon’s MSA helps make explicit six crosscutting issues when generating this new form of evidence. This suggests the need to explore reasons for public values and how decision makers would use such evidence. With an awareness of these issues, evidence on public values has the potential to support upstream policies to tackle health inequalities.